Improved survival after an educational project on colon cancer management in the county of Stockholm – A population based cohort study. Issue 11 (November 2015) - Bernhoff, R.; Martling, A.; Sjövall, A.; Granath, F.; Hohenberger, W.; Holm, T.
Abstract: Introduction: Outcomes in rectal cancer have improved dramatically after the introduction of total mesorectal excision (TME). Recently, the TME concept has been transformed into that of complete mesocolic excision (CME) in an attempt to improve prognosis for patients with colon cancer. Patients and methods: Multidisciplinary team (MDT) workshops including the CME concept were held annually between 2004 and 2008 at the Karolinska University Hospital. The workshops focused on preoperative staging, surgery and histopathology and included lectures and live surgery sessions. To compare survival before and after the "Stockholm Colon Cancer Project" all patients diagnosed with a right sided colon cancer between January 1, 2001 and December 31, 2003 (Group 1) and from January 1, 2006 until December 31, 2008 (Group 2) in Stockholm were identified from the Swedish ColoRectal Cancer Registry (SCRCR). Results: The proportion of patients having a tumour resection and the proportion having emergency surgery was higher in Group 1. There were more early tumours and more R0 resections in Group 2. Overall survival in all diagnosed patients and disease free survival after tumour resection was improved in the second time period. Discussion: Surgical teaching programmes may have an impact on the management and outcome in colon cancer. The exact impact from the "Stockholm Colon Cancer Project" cannot be established, however it is likely that it contributed to the improved survival.